Diagnosis and Treatment of Secondary Hyperparathyroidism in Pre‑Dialysis Stages G3‑G4 Chronic Kidney Disease: A Specialized Survey in Portugal - Ferreira, Ana Carina (2024)
Introduction: The clinical management of secondary hyperparathyroidism (SHPT) in chronic kidney disease (CKD) stages G3‑G4 patients currently faces several challenges. Although the understanding of SHPT has increased exponentially in recent years, many aspects regarding its diagnosis and management in non‑dialysis G3‑G4 CKD remain elusive. Specifically, while it is known that SHPT is linked to vitamin D insufficiency in pre‑dialysis CKD patients, the target levels of vitamin D and parathyroid hormone, SHPT, and vitamin D monitoring and therapeutic guidelines are still to be clarified. It is, consequently, of utmost importance to generate data supporting consensual clinical decision‑making and the implementation of evidence‑based clinical practice guidelines. Methods: Thus, a single‑round Delphi‑like study was conducted herein to assess the opinions and the level of agree‑ ment of 59 Portuguese nephrologists on the diagnosis and treatment of pre‑dialysis G3‑G4 CKD patients with SHPT. Results: Although none of the statements under analysis gathered consensus, more than half of the statements regarding SHPT monitoring and therapeutics focusing on G3‑G4 CKD achieved a qualified majority of agreement/disagreement. Overall, it may indicate a growing consensus trend among Portuguese nephrology specialists. Conversely, the heterogeneity of participants’ opinions regarding the treatment of SHPT‑associated vitamin D insufficiency reflects the heterogeneity in the knowledge in this specific field. Conclusion: The results from this Delphi‑like panel represent a first step towards improving the monitoring and thera‑ peutic strategies concerning the prognosis of G3‑G4 CKD patients, fostering unison among the Portuguese nephrology community.